Simple AI Tools for Personalized Learning: A Qualitative Exploration of Classroom Experiences - Ardian Asyhari; Ghifar Javad H Aziz; Siti Amelia Agustin (AI and Developmental Insights in Education, 2025)
This study investigates how teachers experience the use of simple artificial intelligence (AI) tools in supporting personalized learning, addressing the broader educational challenge of integrating emerging technologies into everyday classroom practice. Using a qualitative phenomenological design, the study draws on semi-structured interviews, classroom observations, and instructional documents from twelve primary and secondary school teachers who regularly employed AI-assisted text simplifiers, writing tools, and automated feedback generators. Data were analyzed using thematic analysis to capture patterns in teachers’ perceptions, instructional decisions, and strategies for validating AI outputs. Three core themes emerged: AI as a catalyst for differentiated content creation, shifts in the feedback process that enable deeper instructional dialogue, and the continued importance of teacher judgment in curating and contextualizing AI-generated material. These findings highlight how AI can enhance personalization and instructional efficiency while reinforcing the pedagogical and ethical role of the teacher in maintaining accuracy and cultural relevance. The study contributes to ongoing debates about AI-enhanced teaching by clarifying how every day, low-complexity tools reshape teacher agency, professional identity, and classroom practice.